Creatures Of Habitat The Changing Nature of Wildlife and Wild Places in Utah and the Intermountain West - Hengesbaugh, Mark (University Press of Colorado, 2001)
From flying squirrels on high wooded plateaus to hanging gardens in redrock canyons, the Intermountain West is home to some of the world's rarest and most fascinating animals and plants. Creatures of Habitat details many unique but little-known talents of this region's strange and wonderful wild inhabitants and descibes their connections with native environments. For example, readers will learn about the pronghorn antelope's supercharged cardiovascular system, a brine shrimp-powered shorebird that each year flies nonstop from the Great Salt Lake to Central Argentina, and a rare mustard plant recently discovered on Mount Ogden. Emphasizing how increasing loss and degradation of habitat hinders native species' survival, Mark Gerard Hengesbaugh discusses what is happening to wildlife and wild places and what is being done about it. Well illustrated, this book has habitat maps, pen-and-ink illustrations, and fifty photos of wildlife and wild places selected by photo editor Dan Miller. Also included are guides to wildlife viewing and lists of Utah species, including those considered sensitive, threatened, or endangered.